2015
DOI: 10.5811/westjem.2015.1.23560
|View full text |Cite
|
Sign up to set email alerts
|

Association of Insurance Status with Health Outcomes Following Traumatic Injury: Statewide Multicenter Analysis

Abstract: IntroductionRecognizing disparities in definitive care for traumatic injuries created by insurance status may help reduce the higher risk of trauma-related mortality in this population. Our objective was to understand the relationship between patients’ insurance status and trauma outcomes.MethodsWe collected data on all patients involved in traumatic injury from eight Level I and 15 Level IV trauma centers, and four non-designated hospitals through Arizona State Trauma Registry between January 1, 2008 and Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 19 publications
(25 reference statements)
4
29
0
Order By: Relevance
“…They consistently pointed to health insurance, which many New Mexicans struggle to access [8,9], especially those in rural areas living far from care, as a related key factor determining trauma patient outcomes. This assertion is consistent with existing literature demonstrating that trauma outcomes are poorer for patients without health insurance at the time of their injury [24,25].…”
Section: Discussionsupporting
confidence: 92%
“…They consistently pointed to health insurance, which many New Mexicans struggle to access [8,9], especially those in rural areas living far from care, as a related key factor determining trauma patient outcomes. This assertion is consistent with existing literature demonstrating that trauma outcomes are poorer for patients without health insurance at the time of their injury [24,25].…”
Section: Discussionsupporting
confidence: 92%
“…1 Socioeconomic disparities in the trauma population have been well documented in the literature, and trauma patients without insurance have been shown repeatedly to have inferior outcomes and higher mortality. [2][3][4][5][6] Unfortunately, there has been a paucity of data in the literature regarding the impact of race and insurance status on trauma patients with severe thoracic trauma.…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to previous studies in which acute trauma patients had increased rates of mortality and complications when they did not have insurance. [9][10][11] Furthermore, previous research showed that obtaining follow-up care can be difficult, 2,3 which seems paramount to patients who are often discharged with the intent to secure outpatient surgical services. Previous research also indicated follow-up was particularly difficult to obtain for those on Medicaid and without insurance.…”
Section: Discussionmentioning
confidence: 99%
“…Along with prolonged instability and potential permanent loss of or decrease in mobility, ankle fractures that do not heal in proper alignment are seven times more likely to develop ankle arthritis, which can cause pain and stiffness requiring long-term treatments. 8 Trauma patients without insurance have increased rates of mortality and complications, [9][10][11] indicating that there may be disparities in accessible care for trauma patients. Understanding barriers to proper care may provide information that could lead to achieving more health equality as dictated by Healthy People 2020 12 and other groups.…”
Section: Introductionmentioning
confidence: 99%